Biofeedback therapy using the Anika computer glove in the rehabilitation of patients with impaired motor function after a stroke (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
To study the effectiveness of biofeedback therapy using the Anika computer gloves in patients with impaired motor function after a stroke.Materials and research methods. During the study, rehabilitation measures were carried out in 41 patients aged 45-70 years with ischemic stroke and functional disorders in the range of motion. In the first group of 13 (31%) patients underwent traditional rehabilitation (physiotherapy, kinesiomassage, ergotherapy). Traditional rehabilitation and  the anika gloves recovery method were  used in 28 (68%) patients of the second group.